2022
DOI: 10.3389/fgene.2022.912510
|View full text |Cite|
|
Sign up to set email alerts
|

The Role of Registers in Increasing Knowledge and Improving Management of Children and Adolescents Affected by Familial Hypercholesterolemia: the LIPIGEN Pediatric Group

Abstract: Pathology registers can be a useful tool to overcome obstacles in the identification and management of familial hypercholesterolemia since childhood. In 2018, the LIPIGEN pediatric group was constituted within the Italian LIPIGEN study to focus on FH subjects under 18 years. This work aimed at discussing its recent progress and early outcomes. Demographic, biochemical, and genetic baseline characteristics were collected, with an in-depth analysis of the genetic defects. The analysis was carried out on 1,602 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…As for genetically diagnosed FH patients (FH/V+), our results showed that high values of both the 12-SNP and 6-SNP scores were associated with increased LDL-c levels, representing one of the possible causes of the extreme variability usually observed among FH patients, even among patients sharing the same pathogenic variant [11,[39][40][41]. The association of these polygenic scores with LDL-c remains debated according to published studies.…”
Section: Discussionmentioning
confidence: 84%
“…As for genetically diagnosed FH patients (FH/V+), our results showed that high values of both the 12-SNP and 6-SNP scores were associated with increased LDL-c levels, representing one of the possible causes of the extreme variability usually observed among FH patients, even among patients sharing the same pathogenic variant [11,[39][40][41]. The association of these polygenic scores with LDL-c remains debated according to published studies.…”
Section: Discussionmentioning
confidence: 84%
“…Unfortunately, lipid and CVD prevention issues are yet poorly known and debated in the young adult population [ 4 ]. Knowledge of the problem, prompt and adequate detection and treatment of subjects with FH in childhood, identification of other CVD risk factors, such as overweight or obesity, hypertension, diabetes and high lipoprotein (a) levels [ 5 ] are milestones in the management of paediatric subjects with FH [ 3 , 6 , 7 ]. Nutritional and lifestyle intervention are first line treatments that have to be started as soon as possible, managed by expert Paediatric Lipidologists at a dedicated Lipid Clinic, involving all the family.…”
Section: Introductionmentioning
confidence: 99%
“…In some centres, dieticians are part of the LIPIGEN staff as well. In 2018, a subgroup of Italian Lipid Clinics involved in the LIPIGEN Network constituted the LIPIGEN Paediatric Group [8]. This sub-study involves both centres specifically dedicated to paediatric patients and adult centres dealing with paediatric patients as well.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the LIPIGEN Paediatric Group is to improve the diagnosis, detection, and treatment of children and adolescents with FH [5]. In October 2021, the LIPIGEN Paediatric Group accounted for over than 1600 subjects aged less than 18 years with a clinical and/or genetic diagnosis of FH who were followed-up by the 30 LIPIGEN centres widely distributed in the whole Italian national territory, with 5 of them specifically dedicated to the paediatric population [8].…”
Section: Introductionmentioning
confidence: 99%